1999
DOI: 10.1211/0022357991772402
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Consequences of the Biphasic Elimination Kinetics for the Diuretic Effect of Furosemide and its Acyl Glucuronide in Humans

Abstract: This review discusses the possibility of whether furosemide acyl glucuronide, a metabolite of furosemide, contributes to the clinical effect of diuresis. First an analytical method (e.g. HPLC) must be available to measure both parent drug and furosemide acyl glucuronide. Then, with correctly treated plasma and urine samples (light protected, pH 5) from volunteers and furosemide-treated patients, the kinetic curves of both furosemide as well as its acyl glucuronide can be measured. The acyl glucuronide is forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…The pharmacokinetics of furosemide is well documented in healthy subjects. Adsorption is rapid and peak levels occur after 60-90 min post-dose and are eliminated by liver and kidney [6]. However, the fast and accurate monitoring of furosemide in bio fluids is important not only in the clinical practice by treatment of patience but also in the field of doping control [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacokinetics of furosemide is well documented in healthy subjects. Adsorption is rapid and peak levels occur after 60-90 min post-dose and are eliminated by liver and kidney [6]. However, the fast and accurate monitoring of furosemide in bio fluids is important not only in the clinical practice by treatment of patience but also in the field of doping control [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This might be due to enterohepatic recirculation of CRA13 because drugs subject to enterohepatic recirculation are often characterized by multiple peaks and a long half-life (e.g., estradiol) (Vree and Timmer, 1998). Likewise, compounds of many other classes such as sulfonamide diuretics (Vree and van der Ven, 1999), antiarrhythmic drugs (Freedman and Somberg, 1991), or nonsteroidal anti-inflammatory drugs (Busch et al, 1995) are also subjected to enterohepatic recirculation. In addition, the bile salts, released after meal ingestion, could have facilitated further dissolution and solubilization of CRA13 [solubility in water, ϳ0.001-0.002 mg/ml; log partition coefficient (log P) ϭ 6.9], allowing a second absorption phase.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, little is known about the mechanisms of FS-induced liver injury. It has been shown that the major metabolic pathway for elimination of FS in both humans and rodents is glucuronidation (Vree and van der Ven, 1999; Williams et al, 2007). Furthermore, FS appears to be metabolized by cytochrome P450s to an epoxide intermediate (Williams et al, 2007) that reacts with proteins in the liver (Mitchell et al, 1974; 1976; Williams et al, 2007).…”
Section: Introductionmentioning
confidence: 99%